Cholangiociliopathies: genetics, molecular mechanisms and potential therapies - Masyuk, Tatyana (2009)
PURPOSE OF REVIEW: The present review summarizes recent knowledge on polycystic liver diseases (PCLDs), mechanisms of hepatic cystogenesis and potential therapies for these conditions. RECENT FINDINGS: PCLD may be classified as cholangiociliopathies. In PCLD associated with polycystic kidney disease, cell proliferation is one of the major mechanisms of cystogenesis, whereas in isolated PCLD (autosomal dominant polycystic liver disease), disrupted cell adhesion may be more important in cyst progression. In cystic cholangiocytes, overexpression of ion transporters and water channels facilitates fluid secretion into the cystic lumen, and growth factors, estrogens and cytokines promote cholangiocyte proliferation. With age, cholangiocytes lining liver cysts acquire features of mesenchymal cells contributing to hepatic fibrocystogenesis. A novel mechanism of liver cyst expansion in PCLD involves microRNA regulatory pathways. Hyperproliferation of cystic cholangiocytes is linked to abnormalities in cell cycle progression and microRNA expression. Decreased levels of miR-15a are coupled to upregulation of its target – the cell cycle regulator, Cdc25A. Cholangiocyte cilia in liver cysts are structurally abnormal. Somatostatin analogues and sirolimus reduce liver cyst volume in PCLD patients. SUMMARY: Clarification of molecular mechanisms of hepatic cystogenesis provides an opportunity for the development of targeted therapeutic options in PCLD.